Hégémonie, masculinité, colonialité - Raewyn Connell (Genre, Sexualité et Société, 2015)
This unpubished paper raises questions about hegemony in gender relations, in the light of the global sociology of knowledge, postcolonial studies of masculinities, and politics of gender reform. It argues for an approach that highlights global power relations, the colonial disruptions of gender orders, and the varying hegemonic projects for masculinity formation that attempt to stabilize gender relations in always-uncertain circumstances.